Health system responsiveness: comparison of different levels of medical institutions in Kunshan City, China - Zhuang Hong; Jing Lu; Gang Chen; Qi Tang; Heqi Sun; Ting Wei; Sitang Zhao; Jun Lu (Annals of Medicine)
Background Evaluation of health system responsiveness (HSR) can improve patient satisfaction, promote health equity and enhance the quality of health services.Objectives To explore the differences in HSR among medical institutions at different levels and in various domains.Methods A multi-stage stratified sampling method was used to select 820 participants aged 18 years and older from Kunshan City, China. Analysis of variance was used for univariate analysis. Linear regression and ordinal logistics were applied to explore the relationship between different hospital levels and HSR. Forest plots were used to illustrate the relationship between each domain and the hospital level.Results The relationship between hospital level and HSR remained significant (p < 0.05). Compared with primary healthcare institutions, secondary hospitals had lower HSR scores (β = -1.47, 95%CI = [-2.15, −0.79], p < 0.001). Similarly, tertiary hospitals had lower HSR scores compared with primary healthcare institutions (β = -1.54, 95%CI = [-2.39, −0.70], p < 0.001). The study found that attention, communication, basic amenities, social support, and the choice of healthcare providers were lower in secondary hospitals compared to primary healthcare institutions (OR < 1; p < 0.05). In tertiary hospitals, attention, communication, autonomy, basic amenities, social support, and the choice of healthcare provider were lower compared to primary healthcare institutions (OR < 1; p < 0.05).Conclusions By comparing the HSR of hospitals at different levels, the study identified areas for improvement. Particularly, urgent improvements are needed in prompt attention, communication, basic amenities, social support and the choice of healthcare providers.